A study of stearyl alcohol bloom on Dan Hill PVC dolls and the influence of temperature. (17th November 2017) - Lauridsen, Clara Bratt; Hansen, Lola Wøhlk; Brock-Nannestad, Theis; Bendix, Jesper; Simonsen, Kim Pilkjær
Abstract : A study was conducted to investigate white bloom found on more than 130 polyvinyl chloride (PVC) dolls from the 1980s and 1990s produced by the Danish factory Dan Hill Plast A/S. The bloom was discovered on the dolls after 10 years of storage in a climate controlled facility with average temperature at 11–12°C and a relative humidity at 50 ± 5%. Analysis of the dolls and the bloom was carried out using Fourier transform infrared spectroscopy, which revealed that the bloom consisted primarily of stearyl alcohol. Subsequent analysis with gas chromatography–mass spectrometry showed a minor presence of cetyl alcohol. It is proposed that the alcohol had been added as a lubricant to aid flow during processing. The stearyl alcohol was almost completely reabsorbed into the PVC dolls following one month storage at room temperature, suggesting that low temperature storage played a decisive role in the appearance of the bloom. It is likely that a decrease in temperature has led to a decrease in compatibility of the stearyl alcohol in the PVC compound, thus promoting its exudation. This paper also discusses an extreme bloom of white crystals on other PVC dolls of unknown provenance.